PREGNANT WOMAN KNOWLEDGE ABOUT TOXOPLASMOSIS IN PUSKESMAS LUBUK BAJA, BATAM CITY - Yusmahenry Galindra; Nanang Rudi Utantyo (Universitas Batam, 2020)
Background : Toxoplasmosis is an infection caused by Toxoplasma gondii. Toxoplasmosis occurs in eating raw or undercooked food, raw or undercooked meat (such as satay, steak), or touching soil or cat feces that contain parasites. Toxoplasmosis is one of the most dangerous infectious diseases in the mother that results in infant disability and fetal death. The purpose of this study was to determine the knowledge of pregnant women about toxoplasmosis. Method : The research method used is descriptive, carried out at the Lubuk Baja Health Center, Batam City, the study was conducted for 6 months, the population in this study were all pregnant women who were in the Lubuk Baja Batam City Health Center with a total sample of 98 people, the sampling technique was carried out by using positive techniques Sampling with research instruments using a questionnaire. Result : The results of the study of 98 respondents, there were 54 respondents (55%) with less knowledge, 32 respondents (32.6%) had sufficient knowledge and 12 respondents (12.2%) had good knowledge. Conclusion : Conclusion more than half of the respondents had less knowledge. It is hoped that pregnant women should seek more information related to toxoplasmosis in order to prevent infection